1).
3*х+12=66
3х= 66-12
3х=54
3х= 54:3
х=18
3*18+12=66
2).
14*(х-10)=84
(х-10)=84:14
(х-10)= 6
х= 6+10
х=16
14*(16-10)=84
3).
(25+х):3=27
(25+х)= 27*3
(25+х)=81
х= 81-25
х=56
(25+56):3=27
4).
92:(36-х)=4
(36-х)= 92:4
(36-х)=23
х= 36-23
х=13
92:(36-13)=4
5).
143-4*х=7
4х=143-7
4х=136
х= 136:4
х=34
143-4*34=7
1).
3*х+12=66
3х= 66-12
3х=54
3х= 54:3
х=18
3*18+12=66
2).
14*(х-10)=84
(х-10)=84:14
(х-10)= 6
х= 6+10
х=16
14*(16-10)=84
3).
(25+х):3=27
(25+х)= 27*3
(25+х)=81
х= 81-25
х=56
(25+56):3=27
4).
92:(36-х)=4
(36-х)= 92:4
(36-х)=23
х= 36-23
х=13
92:(36-13)=4
5).
143-4*х=7
4х=143-7
4х=136
х= 136:4
х=34
143-4*34=7